PENGGUNAAN MEDIA AUDIO VISUAL MELATIH PENDENGARAN DAN DAYA INGAT ANAK USIA DINI DI TK ADE IRMA SURYANI SCHOOL - Nurhayati; Novita Friska; Aminda Tri Handayani; Juli Yanti Harahap (STKIP Subang, 2026)
The problem in this study is that the listening and memory abilities of early childhood students are still relatively low. This is caused by the learning activities conducted by teachers, which still rely on manual teaching materials, picture books, and storytelling. In addition, educational and interactive learning methods have not yet been applied, causing children to become bored and less focused on the learning material. The purpose of this study is to describe the improvement in learning at TK Ade Irma Suryani School through the use of audio (sound) and visual (image) media. The method used in this study is classroom action research (CAR), which was carried out in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The subjects of this study were 15 children from TK Ade Irma Suryani School. Observation sheets were used to collect the necessary data. The results of this study show that the use of audio-visual media in early childhood learning can improve listening and memory skills, especially at TK Ade Irma Suryani School. Through the use of audio-visual media, children became more focused and active during learning activities. Moreover, they were more motivated and enthusiastic in participating in the lessons. Therefore, it can be concluded that the use of audio-visual media is more effective in enhancing the listening and memory skills of early childhood students.